Kinetics of skin temperature in lower limbs of professional soccer athletes - Fernandes, Alex; de Assis, Miller; Marins, João; Andrade, André; Albuquerque, Maicon; Brito, Ciro; da Silva, Cristiano; do Valle, Myrian; Pimenta, Eduardo; Garcia, Emerson (Biology of Sport, 2025)
This study investigated the kinetics of skin temperature (Tsk) in the lower limbs of elite soccer players following official matches, with measurements taken at three time points: pre-game (M1), 24 hours after a match (M2), and 48 hours after a match (M3). Additionally, we explored the correlation between Tsk and individualized creatine kinase (CK) levels. Thirty male athletes from a top-tier professional soccer club were assessed during the Brazilian Serie A Championship. CK levels and Tsk in the lower limbs were recorded at M1, M2, and M3. Tsk was significantly elevated at M2 compared to M1 (P < 0.001) and decreased at M3, although it did not return to baseline levels (P < 0.001). A significant positive correlation was found between Tsk in all regions of interest (ROIs) and the percentage of CK, with the lowest correlation observed at r = 0.52 (P < 0.001). Tsk in the lower limbs showed a pattern similar to CK, being elevated at 24 h after the match and decreasing by 48 h but not fully returning to pre-game levels. These findings suggest that Tsk can complement CK measurements and be useful in training control and recovery strategies for elite soccer athletes.